At a glance: The impact of COVID‐19 on emergency general surgery. Issue 1 (15th January 2021) - Aboul‐Enein, Mohamed Saad; Ishak, Peter; Bhambra, Maninder; Ricart, Pol; Al‐makdase, Lisa; Mourad, Moustafa; Wadley, Martin; Perry, Anthony
Abstract: Aim: This study investigated the impact of COVID‐19 on emergency general surgery practice particularly on referrals, diagnosis, investigations, management pathways, outcomes, patient behaviour and consultant practice. Patients and Methods: Retrospective data collection from two cohorts: 112 patients admitted over 1 week in pre‐COVID period and 90 patients admitted over 1 week during the COVID period. A patient questionnaire and a consultant questionnaire were used to collect data on patient behaviour and consultant practice. Results: The COVID period saw an almost four times and seven times increase in performed X‐rays (CXRs) and CT‐thorax–abdomen–pelvis (TAPs), respectively; 6.5% increase in conservative and 6.2% reduction in surgical management; approximately 50% decline in length of stay (LoS) in conservatively managed patients; 71% of patients' decisions to attend hospital were unaffected; and 78.6% of consultant surgeons preferred to manage patients conservatively. Conclusion: Overall, there were delayed hospital presentations by patients by almost twice as long, an increase in paediatric referrals, a surge in performed scans, and a reduction in hospital stay in patients managed conservatively. Patient behaviour to attend hospital was not heavily influenced by COVID, but consultant practice certainly changed towards more conservative choices. Future studies should explore the impact on paediatric referrals and long‐term effects on surgical training.